Five financial incentives to revive the Gulf of Mexico dead zone and Mississippi basin soils. (1st March 2019) - Tallis, Heather; Polasky, Stephen; Hellmann, Jessica; Springer, Nathaniel P.; Biske, Rich; DeGeus, Dave; Dell, Randal; Doane, Michael; Downes, Lisa; Goldstein, Josh; Hodgman, Tom; Johnson, Kris; et al.
Abstract: A central challenge in the Mississippi River Basin is how to continue to support profitable agricultural production, provide water supply, flood control, transportation, and other benefits, while reducing the current burden of environmental degradation. Several practices have been shown to reduce nutrient runoff and water pollution, and improve soil fertility, while often yielding profits for farmers. Yet many of these beneficial practices remain underutilized. Participants at an expert workshop identified five candidate financial mechanisms that could increase adoption of these beneficial farming practices in four focal Midwest states in the next five years: crop insurance premium subsidies, transformation of the private service provider business model, expansion and targeting of 2019 U.S. Farm Bill funding, development of new state funds, and direction of post-disaster federal funds towards habitat restoration, particularly in floodplains. This study provides rough approximations of the change in nutrient runoff and greenhouse gas (GHG) emissions, the annualized costs, and the nutrient and GHG reductions per dollar likely to result from deployment of each financial mechanism. Based upon these approximations, the adoption of these programs could reduce annual nitrate flows at the outlet of the Ohio and Upper Mississippi River Basins by 25%, surpassing the intermediate 2025 target (20% reduction) and achieving more than half of the long-term target (45% reduction) set by the Mississippi River/Gulf of Mexico Hypoxia Task Force. These approximations also illustrate that these five mechanisms could provide the same GHG reductions (∼43 Tg CO2 e yr −1 ) as taking 12 coal-fired energy plants offline. The total cost of these five financial mechanisms is estimated at ∼2.6 billion, or 64 g of nitrates and ∼17 kg of CO2 e per dollar spent. These proposed solutions all face political, financial, cultural or institutional challenges, but with industry support, creative political action, and continued communication of both private and public benefits, they can create meaningful nutrient reductions and rebuild soils by 2022. Highlights: Financial mechanisms for incentivizing land use practices that reduce impacts in Mississippi River Basin are explored. Five mechanisms with potential to create swift and widespread change are analyzed. These five mechanisms can achieve the intermediate 2025 target for reducing the Gulf of Mexico dead zone. The GHG reductions achieved by these mechanisms would be equivalent to taking 13 coal fired power plants offline. A sliding scale for crop insurance has the largest impact and is also the most cost effective.